Modernity as “passive revolution”: Gramsci and the Fundamental Concepts of Historical Materialism - Thomas, Peter (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractThe recent revival of interest in Marxism within and beyond the academy has led to various proposals for contemporary reconstructions of historical materialism. This article proposes that the work of Antonio Gramsci could provide the basis for an historical materialist interdisciplinary research programme today that is capable of engaging productively in dialogue with other traditions of thought, while respecting their (and its own) differences. The article focuses in particular on Gramsci’s development of the concept of “passive revolution,” arguing that his integration of elements from Marx’s Theses on Feuerbach permits him both to break with various “determinist” deformations of Marx's thought while at the same time insisting upon the integrity of Marxist theory, as a tradition of thought capable of renewal through self-criticism. It proposes that Gramsci's thought offers resources for an explanatory historical narrative of modernity focused upon the political moment as the dialectical unity of “structure” and “agency”.